Menilai Kesehatan Keuangan: Dampak Rasio Lancar, Rasio Utang dan Ekuitas, dan Return Aset terhadap Return Sektor Perbankan - Tarsono, Ono; Mustika, Maya; Mesakh, Asyer Imanuel (Lembaga Penelitian Universitas YARSI, 2025)
This study provides modern insights into the impact of Current Ratio, Debt-to-Equity Ratio, and Return on Assets on stock returns in the banking sector listed on the Indonesia Stock Exchange during 2018–2022. Unlike previous studies that indicated a positive relationship, this study found that these three factors had a negative and significant impact on stock returns. These findings underscore the need for more effective regulatory strategies to manage financial ratios and enhance the attractiveness of stocks in the capital market. A quantitative approach emphasizing numerical data analysis was employed. The study involved 10 conventional commercial banks. Secondary data was used, and it was determined that there were no symptoms of heteroscedasticity. Multiple linear regression analysis revealed that the independent variables Current Ratio, Debt-to-Equity Ratio, and Return on Assets negatively influenced the dependent variable, Stock Returns. The study emphasizes the importance of regulatory recommendations for banking companies to improve asset efficiency and maximize profits to attract higher stock demand. Additionally, the results provide valuable insights for investors, helping them consider financial factors for more informed investment decisions.